Efektivitas konseling kelompok model realita untuk meningkatkan motivasi belajar siswa di sekolah menengan kejuruan - Banowati Banowati; Luh Putu Sri Lestari; Dewi Arum Widhayanti Metra Putri (Jurnal Educatio: Jurnal Pendidikan Indonesia)
This research aims to know the effectiveness of reality counseling to vocational high school.student motivation learning. This research used quantitative research type with quasi eksperiment non equivalrnt control group design. The subject in this researh are 7 student as experimental class category low learning motivation and 7 student as control class. The two class were initially given a pretest, furthermore, only class experimental received treatment reality model group counseling, the control class it funcition as a comparison.  The provision of reality group counseling to the experimental group was carried in 6 meetings after which student with experimental and control were given a post test, to know the effectiveness of reality counseling.  In addiction to analyze this subject, this researh uses effect size. The result of this research shows that Es=11,11, p>0,05. Finally the conclusion is realita group counseling effective can be used increase the learning motivation